Implementasi Bahan Ajar Video Animasi Fabel pada Mata Pelajaran Bahasa Indonesia Terhadap Penguatan Pendidikan Karakter Anak SD - Rohmah, Desiana Maulidatur; Trianita, Mikyal Novi; Hafid, Abdullah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop fable animated video teaching materials in Indonesian Language subjects for strengthening character education in elementary school children. This study employs a qualitative method through a systematic literature review, utilizing journals and books that meet inclusion and exclusion criteria as sources. Data collection was carried out by searching keywords such as “animated video learning,” “fable learning materials,” and “character education in elementary school”. The analysis results indicate that teaching materials play a central role in learning, and the development of engaging teaching materials like